2015
DOI: 10.1080/09540121.2015.1093593
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal ideation and suicide attempts among human immunodeficiency virus-infected adults: differences in risk factors and their implications

Abstract: Many studies have investigated risk factors for suicidal ideation and suicide attempt; however, most have failed to show differences in risk factors between suicidal ideation and suicide attempt among the human immunodeficiency virus (HIV)-infected population. This study was designed to identify differences in risk factors between suicidal ideation and suicide attempts among HIV-infected adults in Seoul. A face-to-face survey of 457 HIV-infected adults was conducted by the Seoul Metropolitan Government in 2013… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
36
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 32 publications
6
36
0
Order By: Relevance
“…This is almost similar to the study done in South Korea, 11% [18]. However, it is higher than community-based studies conducted in Addis Ababa, 0.9% [13], and in Butajira (southern Ethiopia), 3.2% [26].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This is almost similar to the study done in South Korea, 11% [18]. However, it is higher than community-based studies conducted in Addis Ababa, 0.9% [13], and in Butajira (southern Ethiopia), 3.2% [26].…”
Section: Discussionsupporting
confidence: 86%
“…The prevalence of suicidal ideation at Zewditu Memorial Hospital was lower than that in a study conducted in Nigeria, 34.7% [16], UK (southeast London), 31% [17], South Korea, 44% [18], and Texas, 59% [19]. These differences could be attributed to the variation in culture.…”
Section: Discussionmentioning
confidence: 77%
“…Virus infections by human papillomavirus, herpes simplex virus, and Epstein-Barr virus have been associated with an increased risk of OSCC [25, 26]. DDX60 is a type I interferon-inducible gene in response to viral infections [12].…”
Section: Discussionmentioning
confidence: 99%
“…A national registry case control study in Denmark of men who died of suicide (N=9,900) found that suicide risk was associated with comorbid psychiatric illness, recent HIV+ diagnosis, and more intensive and frequent hospital care (Jia, Mehlum & Qin, 2012). A study in Seoul (N=457) found that independent risk factors for SI among HIV+ adults were: young and middle age, living with someone, history of AIDS-defining opportunistic disease, history of treatment for depression, lower social support, and lower psychological status (Kang et al, 2015). Kang et al (2015) found that suicide attempts among PLWHA were independently associated with being a beneficiary of National Medical Aid, economic barriers to treatment, history of treatment for depression, and lower psychological status.…”
Section: Correlates Of Suicidal Ideation and Behaviourmentioning
confidence: 99%